Information Technology in Supervision of Firearms Possession Data Collection at the Directorate of Intelkam Polda Metro Jaya - Seala Syah Alam; A. Josias Simon Runturambi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The ownership of firearms has become an important issue among the TNI/Polri recently. Starting from the arrest of members of the Indonesian Army who ordered people to buy illegal firearms, it proved an indication that firearms were freely sold outside the origins of several military and police officers. Supervision of conventional firearms ownership data collection at DitIntelkam, which is full of convoluted procedures and lengthy stages that take a lot of time, is thought to be one of the factors causing many firearms owners to be reluctant to register their weapons. This study aims to describe the use of digitalization technology. information in an effort to monitor gun ownership to reduce the number of shooting cases with unregistered firearms. The method used in this research is descriptive qualitative involving interviews with research informants and observations of the data collection monitoring process that occurs at DitIntelkam. The findings of this study are that it is time for the conventional system applied at the DitIntelkam of Polda Metro Jaya to carry out a massive transformation on the basis of Information Technology to optimize the monitoring of firearms data collection, especially in the jurisdiction of the Polda Metro Jaya.